The relationship between workplace empowerment and employees’ commitment among support staff at Bintulu Development Authority (BDA) in Bintulu, Sarawak/ Daisy Sudan Kilat - Kilat, Daisy Sudan (2019)
The purpose of this study is to investigate the relationship between workplace empowerment and employees’ commitment among support staff in Bintulu Development Authority (BDA) organization. The factors were derived from the Kanter Structural Empowerment (1993) theory model. For this study, the researcher focuses only on four items such as opportunity, resources, power, and support. Out of 200 sets of questionnaires had been distributed to the employees in BDA, the researcher only received 133 sets of questionnaires which were considered usable with the effective response rate 67%. The result shown that opportunity has positive relationship (r=.573, n=133, p<0.01) with employees’ commitment. There are also had two factors significant with employees’ commitment which is power (r =.567, n=133, p<0.01) and support (r=.511, n=133, p<0.01). Then, followed by resources factor (r=.463, n=133, p<0.01) which shown it has positive relationship with employees’ commitment in BDA organization. In conclusion, Bintulu Development Authority (BDA) organization have practiced the employees' empowerment in the workplace. Kanter’s (1993) helps in provide guidance for understanding empowering and gain a broader perspective and understanding of the empowerment process. Also, the researcher understand better how these structural empowerment factors can affect employees' commitment spirit to always be motivated to withstand work pressure in the workplace.